Website interactivity and processing: Menu customization and sense of agency are keys to better interaction design. Issue 147 (March 2021) - Ahn, Jisoo; Park, Jeong-Min; Lee, Won-Ho; Noh, Ghee-Young
Highlights: Menu customization was effective in enhancing sense of agency. A highlighter tool was not a significant prompt for increasing perceptual bandwidth. Feeling as a source of information is important for learning about air pollution via websites. Abstract: Particulate matter (PM) pollution is a serious issue in Korea, but people are not actively engaged in preventive actions. Therefore, this study aimed to develop a PM website that includes interactive features where users can easily learn PM information; further, we aimed to explore the effects of website interactivity on behavioral intentions. We conducted an online experiment with four versions of a website with differs regarding the presence/absence of menu customization and highlighter options. Data from 100 participants in South Korea showed that menu customization was effective in increasing the users' sense of agency and their intentions to recommend the website, seek more PM information, and engage in the activities of the website owner. However, a highlighter tool was not a significant prompt for enhancing perceptual bandwidth and behavioral intentions. The findings of this study can contribute to the development of interactivity research and models and better website design.